The Americans, the history of a people and a nation - JORDAN, Winthrop D.; Greenblatt, Miriam; Bowes, John S. (Evanston, Ill. : McDougal, Littell, 1985)
A textbook of American history from the arrival of the Indians through the 1980's and the presidency of Ronald Reagan.
Includes bibliographies and index.
Keywords: United States -- History; United States -- History